Heat Shock Protein 27 Plays a Pivotal Role in Myofibroblast Differentiation and in the Development of Bleomycin-Induced Pulmonary Fibrosis - Park, Ah-Mee; Kanai, Kyosuke; Itoh, Tatsuki; Sato, Takao; Tsukui, Tatsuya; Inagaki, Yutaka; Selman, Moises; Matsushima, Kouji; Yoshie, Osamu (PloS one, 2016)
Heat shock protein 27 (HSP27) is a member of the small molecular weight HSP family. Upon treatment with transforming growth factor β1 (TGF-β1), we observed upregulation of HSP27 along with that of α-smooth muscle actin (α-SMA), a marker of myofibroblast differentiation, in cultured human and mouse lung fibroblasts. Furthermore, by using siRNA knockdown, we demonstrated that HSP27 was involved in cell survival and upregulation of fibronectin, osteopontin (OPN) and type 1 collagen, all functional markers of myofibroblast differentiation, in TGF-β1-treated MRC-5 cells. In lung tissues of bleomycin-treated mice, HSP27 was strongly upregulated and substantially co-localized with α-SMA, OPN and type I collagen but not with proSP-C (a marker of type II alveolar epithelial cells), E-cadherin (a marker of epithelial cells) or F4/80 (a marker of macrophages). A similar co-localization of HSP27 and α-SMA was observed in lung tissues of patients with idiopathic pulmonary fibrosis. Furthermore, airway delivery of HSP27 siRNA effectively suppressed bleomycin-induced pulmonary fibrosis in mice. Collectively, our findings indicate that HSP27 is critically involved in myofibroblast differentiation of lung fibroblasts and may be a promising therapeutic target for lung fibrotic diseases.